Phytobiotic additives and their effect on the productive performance of pigs - Caicedo, W.; Chinque, Deisy M.; Grefa, Vanessa J. (Cuban Journal of Agricultural Science, 2022)
Phytobiotics are bioactive principles found in the roots, stems, leaves and fruits of plants and are supplied in the pig diet as essential oils, powders and extracts. These additives are used as food palatability improvers, they increase the secretory production of salivary glands, stomach juices, pancreatic enzymes and hepatic bile acids. They are also involved in the functioning of the enzymes of the intestinal mucosa and intestinal brush border, in gastric and intestinal motility, endocrine stimulation and in antioxidant and anti-inflammatory activity, as well as in intestinal health and productive performance. These compounds show bactericidal effects against Enterococcus faecalis, Clostridium spp., Staphylococcus aureus, Escherichia coli and Salmonella spp. Due to the action they exert on the cell membrane, they cause instabilities that compromise the osmotic balance and cause the lysis of the bacteria. In addition, they show immunomodulatory action, since they can act on T cells, B cells, NK cells (Natural Killer) and macrophages. For these reasons, different researchers are carried out internationally with the aim of evaluating the effect of phytobiotic additives on microbiological, immunological, histological, blood, productive and reproductive indicators in pigs. This review aims to assess the use of phytobiotic additives (essential oils, powders and extracts) in the different stages of pig production. Results of the bioactive components of essential oils, powders, plant extracts and production rates in the different pig categories are shown. Key words: antidiarrheal, antioxidant, bioactive components, plants, intestinal health, pigs